2019
DOI: 10.1177/2235042x19870934
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multimorbidity in community settings: A systematic review and meta-analysis of observational studies

Abstract: Background: With ageing world populations, multimorbidity (presence of two or more chronic diseases in the same individual) becomes a major concern in public health. Although multimorbidity is associated with age, its prevalence varies. This systematic review aimed to summarise and meta-analyse the prevalence of multimorbidity in high, low- and middle-income countries (HICs and LMICs). Methods: Studies were identified by searching electronic databases (Medline, Embase, PsycINFO, Global Health, Web of Science a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
364
5
28

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(428 citation statements)
references
References 93 publications
31
364
5
28
Order By: Relevance
“…There was a weaker association between men with complex multimorbidity and IADL disability compared with women with complex multimorbidity. This is in line with a previous meta-analysis and systematic reviews that have found women to have higher prevalence and to be more strongly associated with multimorbidity compared with men [12,15,16]. The results from this study can be generalized to community-dwelling older populations comparable to the Norwegian setting with low mortality and a high number of older persons.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was a weaker association between men with complex multimorbidity and IADL disability compared with women with complex multimorbidity. This is in line with a previous meta-analysis and systematic reviews that have found women to have higher prevalence and to be more strongly associated with multimorbidity compared with men [12,15,16]. The results from this study can be generalized to community-dwelling older populations comparable to the Norwegian setting with low mortality and a high number of older persons.…”
Section: Discussionsupporting
confidence: 92%
“…Multimorbidity has in systematic reviews been found to be associated with functional decline [9], poor quality of life [10] and increased mortality [11] amongst older persons. There has been found gender and socioeconomic differences where women and lower educated groups have higher prevalence of multimorbidity than men and higher educated groups [12][13][14][15][16]. Both country specific and common global disease combination patterns have been found [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated the prevalence of multimorbidity across countries or regions such as the United States, Australia, Canada, Europe, the Netherlands, Iran, and Mexico, and found that its prevalence varies widely across studies from 12.9% to 95.1% [4][5][6][7][8][9][10][11]. A meta-analysis of research based on 70 community-based studies demonstrated that the overall pooled prevalence of multimorbidity was 33.1% [12]. The burden of medical expenses is growing with the increase in the prevalence of multimorbidity due to the rise in the aging population [13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies have focused on single diseases while ignoring multimorbidity [15][16][17]. Some studies on the prevalence of multimorbidity did not consider the significance of the connection between diseases [18,19]. According to a literature review, most of the recent studies were based on self-reporting of prevalence by specific populations in specific environments, and the sample size was not large enough.…”
Section: Introductionmentioning
confidence: 99%